POTENSI TANAMAN PANGAN DAN PERKEBUNAN UNTUK PENGEMBANGAN WILAYAH KABUPATEN KEPAHIANG - siti mutmaidah (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2018)
This study aims to determine the regional leading sector of Kepahiang Regency as the information and considerations in planning economic development. Secondary data such as time series of the Gross Regional Domestic Product (GRDP) of Kepahiang and Bengkulu in the period 2011-2014 are applied. Klassen Typology and Location Quotient (LQ) are tools of analysis. The results of the analysis based on two analysis tools indicate that the leading sector with the criterias developed, base, and competitive is agricultural sector. The results showed that the agricultural sector can be used as a leading sector in Kepahiang Regency with criteria of the advanced sector and grow rapidly and is the base sector. Seberang Musi Sub-district has the most potential for cultivation of food crops and plantations with 13 commodities that become the base sector. For the specialization of food crop base sector is Kaba wetan Subdistrict with 5 commodities with base criteria and for plantation crops Merigi and Seberang Musi subdistricts with 9 commodities crops.